Coexposure to microplastic and Bisphenol A exhacerbates damage to human kidney proximal tubular cells - Daniela Verzola; Noemi Rumeo; Stefano Alberti; Fabrizio Loiacono; Sebastiano La Maestra; Mario Passalacqua; Cristina Artini; Elisa Russo; Enrico Verrina; Andrea Angeletti; Simona Matarese; Nicoletta Mancianti; et al. (Heliyon)
Microplastics (MPs) accumulate in tissues, including kidney tissue, while Bisphenol A (BPA) is a plasticizer of particular concern. At present, the combined effects of MPs and BPA are unexplored in human renal cells. Therefore, we exposed a proximal tubular cell line (PTECs) to polyethylene (PE)-MPs and BPA, both separately and in combination. When co-exposed, cells showed a significantly reduced cell viability (MTT test) and a pronounced pro-oxidant (MDA levels, NRF2 and NOX4 expression by Western blot) and pro-inflammatory response (IL1β, CCL/CCR2 and CCL/CCR5 mRNAs by RT-PCR), compared to those treated with a single compound. In addition, heat shock protein (HSP90), a chaperone involved in multiple cellular functions, was reduced (by Western Blot and immunocytochemistry), while aryl hydrocarbon receptor (AHR) expression, a transcription factor which binds environmental ligands, was increased (RT-PCR and immunofluorescence). Our research can contribute to the study of the nephrotoxic effects of pollutants and MPs and shed new light on the combined effects of BPA and PE-MPs.